Results From the IQ‐CSRC Prospective Study Support Replacement of the Thorough QT Study by QT Assessment in the Early Clinical Phase. Issue 4 (16th March 2015) - Darpo, B; Benson, C; Dota, C; Ferber, G; Garnett, C; Green, CL; Jarugula, V; Johannesen, L; Keirns, J; Krudys, K; Liu, J; Ortemann‐Renon, C; et al.
Abstract : The QT effects of five "QT‐positive" and one negative drug were tested to evaluate whether exposure–response analysis can detect QT effects in a small study with healthy subjects. Each drug was given to nine subjects (six for placebo) in two dose levels; positive drugs were chosen to cause 10 to 12 ms and 15 to 20 ms QTcF prolongation. The slope of the concentration/ΔQTc effect was significantly positive for ondansetron, quinine, dolasetron, moxifloxacin, and dofetilide. For the lower dose, an effect above 10 ms could not be excluded, i.e., the upper bound of the confidence interval for the predicted mean ΔΔQTcF effect was above 10 ms. For the negative drug, levocetirizine, a ΔΔQTcF effect above 10 ms was excluded at 6‐fold the therapeutic dose. The study provides evidence that robust QT assessment in early‐phase clinical studies can replace the thorough QT study.